Control of local haemostasis with the AngioSeal® vascular closure device in peripheral endovascular interventions via 6-9 F femoral artery access - Machnik, Roman; Pieniążek, Piotr; Musiałek, Piotr; Przewłocki, Tadeusz; Tekieli, Łukasz; Trystuła, Mariusz; Brzychczy, Andrzej; Dzierwa, Karolina; Paluszek, Piotr; Żmudka, Krzysztof; Podolec, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Complications related to the femoral access substantially contribute to peri-procedural morbidity and mortality. Aim: To evaluate whether the use of a collagen plug as a vascular access closure device (AngioSeal ® , AS) influences complications related to the femoral access and duration of hospitalization for peripheral endovascular interventions. Material and methods: Two hundred and one consecutive patients (59.2% male, age 48-87 years) undergoing angioplasty/stenting of the internal carotid, common carotid, vertebral, subclavian, renal, iliac/femoral, innominate artery or cervical-subclavian bypass were randomized (1 : 1 ratio) prior to the intervention to standard manual compression (MC) or AS (6 F or 8 F device used for femoral access with 6-7 F or 8-9 F sheaths respectively). Results : Manual compression was used in 110 patients and AS in 91 patients. There was no difference in the use of 8-9 F and 6-7 F sheats between the two per treatment groups (72.5% vs. 73.6% and 27.5% vs. 26.2%, respectively). Large subcutaneous haematoma, arteriovenous fistula, pseudoaneurysm or femoral artery occlusion requiring surgery occurred in 13.8% MC vs. 4.0% AS for 6-7 F sheaths (p = 0.36) and in 19.7% MC vs. 7.6% AS for 8-9 F sheaths (p = 0.035). Total access site complication rate was 18.2% for MC and 6.6% for AS (p = 0.019). Nine patients with AS (9.9%) required an additional compression dressing ( 12 h). Overall, AS patients were mobilized earlier (2.9 ±2.4 h vs. 14.2 ±2.8 h, p = 0.001) and discharged home earlier after the intervention (33.6 ±14.16 h vs. 68.1 ±34.08 h, p = 0.001). Conclusions : The use of the AngioSeal ® device for femoral access closure during peripheral interventions (AngioSeal ® 8 F for 8-9 F sheath and AngioSeal ® 6 F for 6-7 F sheath) significantly reduces the access site complication rate and allows earlier patient mobilization and discharge from hospital.